Economic integration and the currency and equity markets nexus. (22nd July 2020) - Aftab, Muhammad; Ahmad, Rubi; Ismail, Izlin; Phylaktis, Kate
Abstract: The paper examines the impact of economic integration on the relationship between the currency and equity markets for a group of Asian emerging economies using both linear and non‐linear frameworks. We first derive the dynamic conditional correlations between the two markets and then examine the impact of economic integration on their relationship. Our main results are: (a) there is a negative correlation between real exchange rate changes and equity return differentials for all countries apart from China, which becomes deeper during the global financial crisis (GFC) for some of the countries; (b) economic integration, both real and financial, has an asymmetric impact on the relationship between the two markets both in the short‐run and in the long‐run; and (c) applying a linear framework does not bring out the impact of financial integration.